ANALYZING THE DISTRIBUTION OF POLLUTANTS IN URBAN LANDSCAPES - Shahlokhon Kosimova (American Journals Publishing, 2023)
Environmental quality control is one of the most important functions of environmental protection, as it is aimed at creating reliable information for planning and implementing effective environmental protection measures. Researching environmental monitoring is associated with problems such as large-scale analytical work, large financial costs, imperfect methodological support for environmental situation assessment, multidimensional data bank processing, and others.
Keywords: Environmental situation, effective environmental protection, urban landscapes, environmental control.